1992
DOI: 10.1111/j.1469-1809.1992.tb01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection associated with birth weight. VI. Towards the end of the stabilizing component

Abstract: The secular trend for stabilizing selection on birth weight has been analysed in Italy from 1954 to 1985 in order to study changes in the forces of natural selection which have occurred as a consequence of progress in health care. In previous papers we demonstrated a very rapid relaxation of stabilizing selection on birth weight. In this paper we show that in the last few years this kind of selection has been coming to an end for the vast majority of Italian newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Direct evidence for the action of stabilizing selection in humans is scarcer. Birth weight is one reported example of a human trait under stabilizing selection (22), although the intensity of selection has decreased in postindustrial societies (23). A twin study of female reproductive life-history traits showed evidence for a phenotypic optimum for age at menarche (14).…”
Section: Evidence Of Directional and Stabilizing Selection In Contempmentioning
confidence: 99%
“…Direct evidence for the action of stabilizing selection in humans is scarcer. Birth weight is one reported example of a human trait under stabilizing selection (22), although the intensity of selection has decreased in postindustrial societies (23). A twin study of female reproductive life-history traits showed evidence for a phenotypic optimum for age at menarche (14).…”
Section: Evidence Of Directional and Stabilizing Selection In Contempmentioning
confidence: 99%
“…Human history has shown that, when average infant birth weights are too small or too large, infant mortality is high. As a result, a nice, stable intermediary infant birth weight of 3.5 kg (7–8 lbs) has become the norm and has remained relatively constant over time (Sanjak et al , 2018; Ulizzi and Terrenato, 1992). Similarly, human height continued to increase across subsequent generations (Garcia and Quintana-Domeque, 2007).…”
Section: Organizational Change Is Non-linearmentioning
confidence: 99%
“…Stabilizing selection, in particular, is potentially widespread (Sanjak et al, 2018) and may have contributed to the among‐group differentiation in many skeletal traits (Roseman & Auerbach, 2015). However, direct evidence of stabilizing selection (Nettle, 2002a; Sanjak et al, 2018; Stearns et al, 2010; Stulp et al, 2015; Ulizzi & Terrenato, 1992) and disruptive selection (Beauchamp, 2016; Nettle, 2002b) in humans is rare and is most commonly found with life‐history traits associated with reproductive success. Moreover, throughout the following sections, we discuss phenotypic plasticity as both the ability of a genotype to produce different phenotypes across environments (i.e., genotype‐environment interaction) (Via & Lande, 1985) and the nonheritable plastic response to short‐term environmental conditions (e.g., nutritional differences) that occur during one's lifetime.…”
Section: Introductionmentioning
confidence: 99%